2019
DOI: 10.13189/app.2019.070201
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Fungi in the Public Hand-pump Borehole Water in Onueke, Ezza Local Government Area, Ebonyi State, Nigeria

Abstract: The diversity of fungi in fifteen public hand-pump borehole water in Onueke, Ezza Local Government Area of Ebonyi State, Nigeria was studied during the dry and wet seasons using standard analytical procedures. The total moulds and yeasts counts were 2-8cfu/ml and 1-5cfu/ml respectively during the dry season and 3-12cfu/ml and 1-4cfu/ml respectively during the wet season. More moulds were isolated from the samples during the wet than the dry season while more yeasts were isolated during the dry than the wet sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The calcium hardness values were 0.6-3.4mg/l during the dry season and 1.8-10.4mg/l during the wet season (Tables 3 and 4). All the values were within the WHO standard of 75mg/l for drinking water.Similar results were obtained by Onuorah et al [7] who studied the physicochemical characteristics of public hand-pump boreholes in Onueke, Ebonyi State, Nigeria.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The calcium hardness values were 0.6-3.4mg/l during the dry season and 1.8-10.4mg/l during the wet season (Tables 3 and 4). All the values were within the WHO standard of 75mg/l for drinking water.Similar results were obtained by Onuorah et al [7] who studied the physicochemical characteristics of public hand-pump boreholes in Onueke, Ebonyi State, Nigeria.…”
Section: Discussionsupporting
confidence: 87%
“…The values for the total suspended solids were 0.00-0.25mg/l during the dry season and 0.03-2.01mg/l during the wet season (Tables 1 and 2). The values for both seasons were within the WHO permissible limit of 30mg/l for drinking water .Onuorah et al [7] reported the total suspended solids values of 0.01-0.84mg/l and 0.01-0.48mg/l during the dry and wet seasons respectively for the borehole water samples they analysed. Onwughara et al [20] however reported that the total suspended solids of the samples they analysed ranged from 31.3-55.0mg/l.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations